Lateralization of Color Discrimination Performance and Lexical Effects in Patients With Chronic Schizophrenia - Kogata, Tomohiro; Iidaka, Tetsuya (Frontiers in Human Neuroscience, 2021)
Introduction: Patients with schizophrenia experience various visual disturbances. However, information regarding color perception in these patients is rare. In this study, we used a lateralized color search task to investigate whether difference in color name affects color recognition in patients with schizophrenia. Methods: In a color search task, we controlled the position of the target that emerged from the left visual field (LVF) or right visual field (RVF) as well as the color category. In this task, both the target and the distractors had the same or different color name (e.g., blue or green). Results: Patients with schizophrenia showed faster performance in the color search task with different color names for target-distractors when the target emerged from the LVF than when it emerged from the RVF. However, the same laterality was not observed in healthy controls. This finding indicates that semantic processing for color name differences influenced visual discrimination performance in patients with schizophrenia more profoundly in the LVF than in the RVF. Conclusion: This lateralized performance could imply the failure of the left hemisphere language processing dominance in schizophrenia. A search paradigm combining target position and category may indicate that automatic language processing depends on imbalanced hemispheric function in schizophrenia.